ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN BAHAN BAKAR MINYAK PERTALITE - Halim, Abdul; Afkarina, Dina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
The research method was used to collect data from 248 active users of Gas Stations in Balikpapan City. Sampling was done gradually and randomly to encompass sufficient population variation of Gas Station users. Multiple regression analysis was used to analyze the relationship between independent and dependent variables. The research results indicate that product quality and price have a significant influence on customer satisfaction at Gas Stations in Balikpapan City. These findings underscore the importance of managing and improving the quality of products as well as competitive pricing of Partalite heating oil products to meet customer expectations and needs. Based on the analysis results, it is concluded that efforts to improve customer satisfaction at Gas Stations in Balikpapan City should focus on improving product quality and adjusting prices more reasonably. Suggestions for enhancing customer satisfaction include developing more effective marketing strategies, enhancing employee training to provide quality service, and implementing customer loyalty programs to strengthen long-term relationships with consumers. The findings of this research are expected to provide valuable insights to gas station operators and other stakeholders in the heating oil industry to enhance customer satisfaction and maintain a competitive market share.